A novel SOI pressure sensor for high temperature application. (1st January 2015) - Li, Sainan; Liang, Ting; Wang, Wei; Hong, Yingping; Zheng, Tingli; Xiong, Jijun
Abstract The silicon on insulator (SOI) high temperature pressure sensor is a novel pressure sensor with high-performance and high-quality. A structure of a SOI high-temperature pressure sensor is presented in this paper. The key factors including doping concentration and power are analyzed. The process of the sensor is designed with the critical process parameters set appropriately. The test result at room temperature and high temperature shows that nonlinear error below is 0.1%, and hysteresis is less than 0.5%. High temperature measuring results show that the sensor can be used for from room temperature to 350 °C in harsh environments. It offers a reference for the development of high temperature piezoresistive pressure sensors.